FORMATION OF STUDENTS' PRINCIPLES OF ECOLOGICAL CULTURE AND SUSTAINABLE DEVELOPMENT (Scientific journal of the Fergana State University, 2025)
This article examines the issues of developing students' ecological culture and implementing sustainable development principles. The study analyzes modern trends in ecological education, its challenges, and scientific approaches to fostering environmental awareness and culture. Additionally, the views of researchers in the field of ecological education, the current situation, and future forecasts based on mathematical analysis are presented. The research has been expanded with practical experiences in ecological education and new scientific sources.